Design and build mini refrigerator with VDI 2222 method - Abbas, Aries; Winoto, Rifal Budi (Jurnal Info Sains : Informatika dan Sains, 2024)
Mini refrigerators are now starting to be in great demand among people nowadays because they are easy to carry/place where we want and maintenance is quite easy, the more there are developments starting from the technology used and the varied designs. The development of the mini refrigerator uses the method used in designing the mini refrigerator test equipment using the VDI 2222 design method. By using this method we can find out more clearly the use of this mini refrigerator, such as maintenance of the mini refrigerator, the use of the mini refrigerator itself, how to operate it properly and correctly, getting to know the components of a mini refrigerator, knowing the uses of mini refrigerator components. The general image of a refrigerator is a tool that is used to cool or also to preserve food or drinks because at low temperatures the growth of bacteria will be inhibited. The components of this mini refrigerator consist of a frame to support the styrofoam and the electrical consists of what will be used, namely the switch and power supply, the module used is a pro module which only has one set of thermoelectric modules which will then work with the electrical then transferred to the switch. and later it goes to the power supply which will be processed into a mini refrigerator where the test results are carried out.